Why increasing availability of ART is not enough: a rapid, community-based study on how HIV-related stigma impacts engagement to care in rural South Africa. (December 2015) - Treves-Kagan, Sarah; Steward, Wayne; Ntswane, Lebogang; Haller, Robin; Gilvydis, Jennifer; Gulati, Harnik; Barnhart, Scott; Lippman, Sheri
Abstract Background Stigma is a known barrier to HIV testing and care. Because access to antiretroviral therapy reduces overt illness and mortality, some scholars theorized that HIV-related stigma would decrease as treatment availability increased. However, the association between ART accessibility and stigma has not been as straightforward as originally predicted. Methods We conducted a "situational analysis"—a rapid, community-based qualitative assessment to inform a combination HIV prevention program in high prevalence communities. In the context of this community-based research, we conducted semi-structured interviews and focus groups with 684 individuals in four low-resource sub-districts in North West Province, South Africa. In addition to using this data to inform programming, we examined the impact of stigma on the uptake of services. Results Findings suggested that anticipated stigma remains a barrier to care. Although participants reported less enacted stigma, or hostility toward people living with HIV, they also felt that HIV remains synonymous with promiscuity and infidelity. Participants described community members taking steps to avoid being identified as HIV-positive, including avoiding healthcare facilities entirely, using traditional healers, or paying for private doctors. Such behaviors led to delays in testing and accessing care, and problems adhering to medications, especially for men and youth with no other health condition that could plausibly account for their utilization of medical services. Conclusions We conclude that providing access to ART alone will not end HIV-related stigma. Instead, individuals will remain hesitant to seek care as long as they fear that doing so will lead to prejudice and discrimination. It is critical to combat this trend by increasing cultural acceptance of being seropositive, integrating HIV care into general primary care and normalizing men and youths' accessing health care.